The Non-Support Nature of the Legal Right Share in Colombia - Alarcón-Palacio, Yadira Elena; Pontificia Universidad Javeriana (Pontificia Universidad Javeriana, 2015)
This work aims to solve a currently very conflictive issue regarding the inheritance rights of the spouse or surviving common law spouse: the legal nature of the legal right share. Specifically, we will focus our study on the classic current, characterized by giving the legal right share a sup- port nature, and by means of an inductive-deductive analysis we come to determine that this nature is not applicable to the legal right share. This is due to the impossibility to fit in the mandatory characteristics and assumptions of support obligations. Thus, legal right share has to be understood as an inheritance institution in nature, consisting of the inheritance, with or without a will, to the spouse or common law spouse, in all inheritance orders. The legal right share corresponds to considering an inheritance by law, constituted for support purposes, in favor of the spouse or common law spouse, in all orders.